2004
DOI: 10.1111/j.0953-816x.2004.03315.x
|View full text |Cite
|
Sign up to set email alerts
|

Correspondence of AQP4 expression and hypoxic‐ischaemic brain oedema monitored by magnetic resonance imaging in the immature and juvenile rat

Abstract: Whether the water channel protein AQP4 is involved in the very early cell swelling and brain oedema observed with cerebral hypoxia-ischaemia (HI) and whether this response depends on the maturity of brain were investigated by comparing regional changes in AQP4 protein expression and signal intensity on magnetic resonance (MR) images in immature and juvenile brains. Maps of T2 and the apparent diffusion coefficient (ADC) of water were acquired in 1- and 4-week-old rats at times prior to HI, within the last 5 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
62
3
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 32 publications
10
62
3
2
Order By: Relevance
“…Notably, the changes in AQP4 expression paralleled the changes in edema as demonstrated on MRI (15,18,19). Upregulation of AQP4 may occur during trauma-induced cytotoxic edema in rats, and the outcome becomes worse with the upregulation of AQP4 (8), whereas edema is less severe with the downregulation or knockout of AQP4 during cytotoxic edema (20,21).…”
Section: Introductionmentioning
confidence: 71%
“…Notably, the changes in AQP4 expression paralleled the changes in edema as demonstrated on MRI (15,18,19). Upregulation of AQP4 may occur during trauma-induced cytotoxic edema in rats, and the outcome becomes worse with the upregulation of AQP4 (8), whereas edema is less severe with the downregulation or knockout of AQP4 during cytotoxic edema (20,21).…”
Section: Introductionmentioning
confidence: 71%
“…Up-regulated AQP4 expression was also found in penetrating brain injury in rats (4) and in cortical contusion injury (3). Other studies show reduced AQP4 expression in response to various insults, including transient middle cerebral artery occlusion in rats (20,21) and diffuse (22) and focal (23) head trauma. Notwithstanding some conflicting results in the literature regarding the direction of change in AQP4 expression in various pathologies, it is concluded that brain AQP4 expression is sensitive to many types of insults, which, from the functional data here, translates to altered brain water balance.…”
Section: Discussionmentioning
confidence: 87%
“…The specific anatomical and cellular localization of aquaporin 4 (AQP 4) water channels in the central nervous system suggests that this protein plays a crucial role in the cerebral water balance . Recently, the role of AQP4 in maintaining water homeostasis during the development of post-traumatic or ischemic brain edema has been described, although conflicting results have been obtained using different models (Hu et al, 2005;Ke et al, 2001;Kiening et al, 2002;Lu and Sun, 2003;Manley et al, 2000;Meng et al, 2004;Sato et al, 2000;Sun et al, 2003;Taniguchi et al, 2000;Vizuete et al, 1999).…”
Section: Introductionmentioning
confidence: 99%